دراسة الخصائص البصرية والبنيوية لأغشية أكسيد النيكل المطعمة بالألمنيوم - غرايسة, فاطمة الزهرة; قصير, ريان (university of eloued جامعة الوادي, 2023)
تضمن هذا العمعل دراسعة الدصعائ البنيويعة، الضعوئية والكهربائيعة عية رقيقعة معن أ سعيد النيكعل 10 ( و لك انطلاقا من مادت نترات -08-06-04-02- بنس (% 00 )Al والمطعم با لمنيوا )NiO النق حيعث تعم ترسعي محلعوا المعادتين )Al (NO3 3 .9H2O) ونترات ا لمنيوا )Ni (NO3)2 .6H2O النيكل 450 ( بتقنية الرب باانحلاا الكيميائ الحرار ، أرهرت نتائ C° على ر ائز زجاجية تحت درجة حرارة انعراج ا شعة السينية أن ا ية المحضرة ات تر ي بلعور مكعبع فع ااتجعاه المفضعل 200 ( لجميع - 912.04cm- وجعود رابطتعين يميعائيتين فع نطعا التعرددات ( 1 )FTIR ا ية. بينت نتعائ فحوصعات وال انية تععزى )O-H أو )N-H 756.086-766.114 (، القمة ا ولى قد تكون إما إلى cm- 900.57 ( و 1 أما فيما يتعلق ،(DRX) ورجحت أن تكون سيد النيكل حس نتائ )Ni-O أو )Al-O أن تكون إما إلى -4- فقد أرهرت تحس ن ا ف شفافية العينات المطعمعة بعا لمنيوا عنعد نسع التطععيم (% 2 )UV-VIS بالنتائ 10 ( التع قاربعت % 95 وهع تدع أعلعى نسعبة تطععيم % 10 (، وبالنسعبة للمقاوميعة السعطحية فقعد شعهدت ارتفاعا بيرا بعد التطعيم.This work included a study of the structural, optical and electrical properties of thin films of pure nickel oxide (NiO) and doped with aluminum (Al) with percentages (00-02-04-06-08-10 %). It was based on the two materials, nickel nitrate (Ni (NO3)2 .6 H2O) and aluminum nitrate (Ni (NO3)3 .9 H2O), where a solution of the two materials was deposited on glass substrates under a temperature (450°C) by chemical spray pyrolysis technique. The X-ray diffraction results showed that the prepared films have a cubic crystalline structure in the preferred direction (200) for all films. The results of the FTIR tests showed the presence of two chemical bonds in frequency range 766.114-756.086 cm-1 and 912.04-900.57 cm-1, the first peak may be either(N-H) or(O-H) and the second is attributed to being (Ni-O) or (Al-O) and it was likely to be the Nickel oxide according to )DRX results. The results of (UV-VIS) showed an improvement in the transparency of the doped samples with aluminum at the doping percentages (%) (2-4-10), which approached 95%, and it belongs to the highest doping percentage (10%), and as for the surface resistance, it witnessed a significant increase after doping.
مذكرة ماستر فيزياء
Keywords: أ ية رقيقة، أ سيد النيكل، تقنية الرب باانحلاا الحرار ، انعراج ا شعة السينية .)Al التطعيم با لمنيوا ،)UV-VIS ،)FTIR ،)DRX; hin films, nickel oxide, chemical spray pyrolysis technique, X-ray diffraction (DRX), (FTIR), (UV-VIS), aluminum (Al) doping.